Housing wealth and wage bargaining - Chris Cunningham; Robert R. Reed (Federal Reserve Bank of Atlanta, 2012)
We examine the relationship between housing equity and wage earnings. We first provide a simple model of wage bargaining where failure leads to both job loss and mortgage default. Moreover, foreclosure generates disutility beyond selling a home. We test this prediction using nine waves of the national American Housing Survey. Employing a rich set of time and place controls, individual fixed effects, and an instrumental variable strategy, we find that people with an underwater mortgage command a significantly lower wage than other homeowners. This finding survives a number of robustness checks. We also include other determinants of house lock such as a favorable mortgage interest rate relative to the current rate and a capped property tax assessment, but we do not find these factors lower earnings. We conclude that negative equity matters because default is unpleasant or costly, not because it precludes an out-of-state job search.
Keywords: D10; J30; R20; 330; negative equity; wages; mortgage default